Ilhas de calor urbanas em Sorocaba/SP: uma abordagem com base no sistema das zonas climáticas locais - Santos, Fernanda Frois dos (2023)
The urbanization of cities increases as climate disruptions occur at the local scale. Therefore, it is considered important to study the dynamics of cities and the relationship between the urban climate, since it is on this scale that profound transformations take place. In view of this, this work aimed to analyze the surface heat islands and the urban canopy layer in Sorocaba/SP, based on the classification of LCZs in the municipality. The following methodologies were used: detection of surface heat islands through thermal images from the Landsat 8 satellite, definition of LCZs through the LCZ generating system, measurement of air temperature and relative air humidity through mobile transects and categorization of intensities of climatic heat islands. The results demonstrated that surface heat islands and climatic heat islands of fragility, medium and strong magnitudes occur in compact lowrise LCZs (LCZ3) throughout the urban patch. It was concluded that there are heat islands in Sorocaba.